2015
DOI: 10.5714/cl.2015.16.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Mesophase formation behavior in petroleum residues

Abstract: Mesophase pitch is an important starting material for making a wide spectrum of industrial and advanced carbon products. It is produced by pyrolysis of petroleum residues. In this work, mesophase formation behavior in petroleum residues was studied to prepare environmentally-benign mesophase pitches, and the composition of petroleum residues and its influence on the mesophase formation was investigated. Two petroleum residues, i.e., clarified oil s (CLO-1, CLO-2) obtained from fluid catalytic cracking units of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 33 publications
0
5
0
2
Order By: Relevance
“…So, it can maintain the fluidity of the CTP 3 during high‐temperature carbonization. [ 34,35 ] At the same time, CD contained a large amount of H γ and a certain amount of H n . It showed that the main structure of hydrogenated coal diesel contained a certain amount of alkanes and naphthenes.…”
Section: Resultsmentioning
confidence: 99%
“…So, it can maintain the fluidity of the CTP 3 during high‐temperature carbonization. [ 34,35 ] At the same time, CD contained a large amount of H γ and a certain amount of H n . It showed that the main structure of hydrogenated coal diesel contained a certain amount of alkanes and naphthenes.…”
Section: Resultsmentioning
confidence: 99%
“…FT-IR spectroscopy is also a useful technique to calculate aromaticity index of two different pitches by taking absorbance value at 3050 cm −1 and 2920 cm −1 . The aromaticity index of pitches was calculated by following equation I ar = Abs 3050 /(Abs 3050 + Abs 2920 ) [10,12] which is presented in Fig. 4.…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…상기 고분자 용액을 실온까지 식힌 후, AAc (15 mL), GA (1 mL), EGDMA (1.5 mL), 및 KPS (2 wt% dissolved in water, 1 mL) 를 첨가하고, 이를 실온에서 3 min 동안 교반하였다. 또한, 메조페이 스 핏치는 탄소물질의 가교결합의 증가 및 고온 열처리 동안에 심하 게 팽창되는 것을 억제하기 위하여 300 ℃에서 2 h 동안 공기분위기 에서 안정화 반응을 진행하였다 [23,24]. 이렇게 제조된 100 µm 이하 …”
Section: 메조페이스 핏치기반 그라파이트 폼의 제조unclassified